Assessment of Dental Caries and Periodontal Status Among Patients with Dental Fluorosis Visiting A Dental College, Chennai. - FAUZI, NUR QISTINA BINTI AHMAD; KUMAR R, PRADEEP; GURUNATHAN, DEEPA (The journal of contemporary issues in business and government, 2021)
Fluoride (F) is known to be one of the various chemicals that have proven to leave substantial effects to the human body especially through our drinking water. This chemical can be described as a double edged sword since in its deficiency, it enables the formation of dental caries while in excess, it can result in both dental and skeletal fluorosis. The aim of this study was to analyse both the dental caries and periodontal status in dental fluorosis patients. A total of 182 patients who were diagnosed with dental fluorosis was evaluated. Their age, gender, DMFT index and periodontal status was obtained from the patient records from the institution between June 2019 to March 2020. Results were analysed and compared using the SPSS Statistical Software by doing both the frequency tests and correlation tests (Chi-square test). In this study, we observed that there is negative association between dental caries (p=0.70) and the periodontal status (p=0.20) with dental fluorosis. Within the limits of the study, there is no significant association between the severity of dental caries and periodontal status with dental fluorosis. However, dental fluorosis is at a higher prevalence in males and at an age group of 21-25 years old.